Perbandingan Tanggung Jawab Hukum Dokter dalam Kasus Malpraktik Medis antara Hukum Pidana dan Perdata - Manambak Silalahi; Bambang Kuntjoro; M.Izzaddin Arief Setyawan; M. Saefuddin; Persia Misuari; Syafrida (Himpunan Ilmu Hukum dan Ilmu Hukum Islam, 2026)
Medical malpractice is a legal problem that is getting more and more attention because it can cause losses for patients as well as implications for the legal liability of doctors. In the practice of health services, the relationship between doctor and patient is born through a therapeutic agreement that gives rise to rights and obligations for the parties. If there are deviations from professional standards, service standards, or standard operating procedures, doctors can be held accountable both in the realm of criminal law and civil law. This study aims to analyze and compare the legal responsibilities of doctors in medical malpractice cases based on the perspective of criminal law and civil law in Indonesia. The research method used is normative juridical with a legislative approach and a conceptual approach. The data used is in the form of secondary data consisting of primary, secondary and tertiary legal materials that are analyzed juridically qualitatively. The results of the study show that the criminal liability of doctors is based on the existence of mistakes that meet the elements of criminal acts as well as the causal relationship between medical actions and the losses caused. Meanwhile, civil liability is oriented towards recovering patient losses through default mechanisms and unlawful acts. Law Number 17 of 2023 concerning Health emphasizes that the assessment of medical personnel errors must be based on compliance with professional standards, service standards and operational procedure standards. Therefore, the application of dual liability must be carried out proportionately by considering criminal, civil, ethical and professional discipline aspects in order to realize legal certainty and balanced protection for doctors and patients.